Can simple mobile phone applications provide reliable counts of respiratory rates in sick infants and children? An initial evaluation of three new applications. Issue 5 (May 2015) - Black, James; Gerdtz, Marie; Nicholson, Pat; Crellin, Dianne; Browning, Laura; Simpson, Julie; Bell, Lauren; Santamaria, Nick
Abstract Background Respiratory rate is an important sign that is commonly either not recorded or recorded incorrectly. Mobile phone ownership is increasing even in resource-poor settings. Phone applications may improve the accuracy and ease of counting of respiratory rates. Objectives The study assessed the reliability and initial users' impressions of four mobile phone respiratory timer approaches, compared to a 60-second count by the same participants. Methods Three mobile applications (applying four different counting approaches plus a standard 60-second count) were created using the Java Mobile Edition and tested on Nokia C1-01 phones. Apart from the 60-second timer application, the others included a counter based on the time for ten breaths, and three based on the time interval between breaths ('Once-per-Breath', in which the user presses for each breath and the application calculates the rate after 10 or 20 breaths, or after 60 s). Nursing and physiotherapy students used the applications to count respiratory rates in a set of brief video recordings of children with different respiratory illnesses. Limits of agreement (compared to the same participant's standard 60-second count), intra-class correlation coefficients and standard errors of measurement were calculated to compare the reliability of the four approaches, and a usability questionnaire was completed by the participants. Results There was considerable variation in the counts, with large components of the variation related to the participants and the videos, as well as the methods. None of the methods was entirely reliable, with no limits of agreement better than −10 to +9 breaths/min. Some of the methods were superior to the others, with ICCs from 0.24 to 0.92. By ICC the Once-per-Breath 60-second count and the Once-per-Breath 20-breath count were the most consistent, better even than the 60-second count by the participants. The 10-breath approaches performed least well. Users' initial impressions were positive, with little difference between the applications found. Conclusions This study provides evidence that applications running on simple phones can be used to count respiratory rates in children. The Once-per-Breath methods are the most reliable, outperforming the 60-second count. For children with raised respiratory rates the 20-breath version of the Once-per-Breath method is faster, so it is a more suitable option where health workers are under time pressure.